A new species of Cortinarius subg. Telamonia (Agaricales) from Yunnan, China - Yang, Yi-Wen; Li, Tai-Shun; Zhao, Qi; Zhang, Ying (Phytotaxa, 2025)
Cortinarius represents not only the most extensive genus within the Agaricales but also constitutes a significant ectomycorrhizal lineage, a crucial ectomycorrhizal genus for maintaining ecosystem functionality. During a field survey in the Three Parallel Rivers Region, China, two specimens of Cortinarius were collected from an Abies forest. Based on morphological and phylogenetic analysis of ITS and nrLSU sequences, a novel species, Cortinarius orientiprivignipallens, is classified within the subgenus Telamonia, section Privignati. This species is characterized by its fibrillose pileus surface, which is greyish-white and becomes glabrous as it matures; the stipe is greyish-violet at the apex, while remnants of the universal veil appear brown. A description, illustration, phylogenetic analysis results, and comparison with allied taxa are provided. In addition, a key to the 20 new species of Cortinarius subgenus Telamonia published in China from 2019 to 2025 is also provided.